Assembly Codes : The Logistics of Media - Zieger, Susan Marjorie; Starosielski, Nicole, 1984-; Hockenberry, Matthew Curtis, 1982- (Book collections on Project MUSE., 2021)
"Assembly Codes connects the critical study of logistics to the field of media and communications studies. It documents how logistics-the techniques of organizing and coordinating the movement of materials, bodies, and information-has had a substantial effect on how media is produced, distributed, and consumed, ranging from the logistics of film production to the construction of digital networks. It reveals how logistical technologies have generated new ways of seeing, and new aesthetic and performative practices. Additionally, the essays reveal how media technologies themselves, from phone systems to software, underpin global production"--